Student Academic Procrastination That Boils Down to Gadget Addiction: Post-Pandemic Challenges to Solve - Wahyuni, Sri; Hura, Rosnila; Simanjuntak, Herbin; Zendrato, Muliani; Purba, Vernando; Sitepu, Meri KD (LP. Ma'arif Janggan Magetan, 2022)
The prolonged pandemic conditions experienced by the world forced changes in various aspects of life and unwittingly formed a new